2003
DOI: 10.1021/ma034830j
|View full text |Cite
|
Sign up to set email alerts
|

Butadiene Insertion and Constitutional Units in Ethene Copolymerizations by C2-Symmetric Metallocenes

Abstract: Copolymerizations of ethylene with 1,3-butadiene in the presence of catalytic systems based on some C 2-symmetric zirconocenes (rac-[CH2(3-R-1-indenyl)2]ZrCl2 where R = −C(CH3)3 (1), −CH(CH3)2 (2), −CH2CH3 (3), −CH3 (4), and −H (5)) are compared. The chemical nature and the relative amount of constitutional comonomer units from butadiene are strongly affected by the bulkiness of the substituent in positions 3 and 3‘. DFT calculations indicate that the observed dependence of constitutional units from butadiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…Chemical shifts were referenced to the residual solvent peak (δ1H = 7.15 ppm). Quantity of the vinyl groups Equation (7) and the internal olefins Equation (8) in ethylene/butadiene copolymers were quantified as per 1000 Carbon in accordance with the following Equations (7) and (8) C-NMR spectra of the propylene/butadiene copolymers were recorded on an ECA500 spectrometer (125 MHz) from Japan Electron Optics Laboratory Co. Ltd. (JEOL, Tokyo, Japan), using 1,1,2,2-tetrachloroethane-d2 as a solvent at 140 °C. Chemical shifts were referenced to the residual solvent peak (δ13C = 72.4 ppm).…”
Section: Polymer Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemical shifts were referenced to the residual solvent peak (δ1H = 7.15 ppm). Quantity of the vinyl groups Equation (7) and the internal olefins Equation (8) in ethylene/butadiene copolymers were quantified as per 1000 Carbon in accordance with the following Equations (7) and (8) C-NMR spectra of the propylene/butadiene copolymers were recorded on an ECA500 spectrometer (125 MHz) from Japan Electron Optics Laboratory Co. Ltd. (JEOL, Tokyo, Japan), using 1,1,2,2-tetrachloroethane-d2 as a solvent at 140 °C. Chemical shifts were referenced to the residual solvent peak (δ13C = 72.4 ppm).…”
Section: Polymer Characterizationmentioning
confidence: 99%
“…Chemical shifts were referenced to the residual solvent peak (δ13C = 72.4 ppm). The spectrum was analyzed with reference to the chemical shifts of the signals assigned to the vinyl groups, the cyclopropane skeleton, the methylcyclopentane skeleton [19], the 1,4-addition units and the 1,3-addition units in the propylene/butadiene copolymers which were described in previous papers [8,10,11]. The determination of the butadiene content (Equation (9)) and the vinyl groups content (Equation (10)), the cyclopropane skeleton content (Equation (11)), the methylcyclopentane skeleton content (Equation (12)), the 1,4-addition units content (Equation (13)), the 1,3-addition units content (Equation (14)), and the hydrogenated 1,4-addition units content (Equation (15)) relative to all the butadiene-derived structural units was performed in accordance with the following Equations (9) to (15).…”
Section: Polymer Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7] As it has been reported in the literature, PEs containing controlled amounts of methylene-1,2-cyclopropane and methylene-1,2-cyclopentane units (hereafter called E-C3) can be obtained by the polymerization of ethene with 1,3-butadiene using rac-[CH 2 (3-tert-butyl-1-indenyl) 2 ]ZrCl 2 activated by methylalluminoxane as a catalyst. [8][9][10][11][12] These PEs are technologically relevant because the presence of reactive cyclopropane rings in the chains discloses the possibility to obtain polymers with different properties. 13,14 For example, in a recent study by our group, we showed that it is possible to produce crosslinked PE by simple thermal treatments of E-C3 copolymers in the temperature range of 160-200 1C.…”
Section: Introductionmentioning
confidence: 99%